2014
DOI: 10.1111/soc4.12213
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Wage Gap in the United States and Cross Nationally

Abstract: Scholarship in sociology and economics has long explored the gender wage gap. Recent research suggests that these inequalities are indicative of important differences not only between men and women, but among women and men, ref lecting rising levels of income inequality among workers in the postindustrial era. We argue that the most interesting debates in the gender wage gap -those exploring differences among subgroups by class, race, and/or parenthood status (such as the motherhood wage penalty), as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 128 publications
(206 reference statements)
0
29
0
1
Order By: Relevance
“…While research on the gender wage gap suggested that much of “women's gains” are better understood as “men's losses” (e.g. Bernhardt, Morris and Handcock ; Misra and Murray‐Close ), on the domestic front, some of men's gains might be similarly understood as women's losses (see Figure ).…”
Section: Marriageability Among Middle‐ and Upper‐class Menmentioning
confidence: 99%
“…While research on the gender wage gap suggested that much of “women's gains” are better understood as “men's losses” (e.g. Bernhardt, Morris and Handcock ; Misra and Murray‐Close ), on the domestic front, some of men's gains might be similarly understood as women's losses (see Figure ).…”
Section: Marriageability Among Middle‐ and Upper‐class Menmentioning
confidence: 99%
“…Both structural and cultural factors play a role in maintaining the relationship between parenthood and gender‐traditional work and family arrangements. State policies that support male breadwinner and female caregiver families (Crompton, ; Lewis, ), a gender wage gap that favors men (Misra & Murray‐Close, ), the ability to access quality paid child care (Boeckmann et al, 2014), and the availability of cultural support for working mothers or caregiving fathers (Boeckmann et al, ; Kramer & Kramer, ) all influence parents' participation in paid work and caregiving.…”
mentioning
confidence: 99%
“…If one were just to eyeball a chart showing average wages over time, 5 one would see that white men earn more than white women, and more than black and Latino men, whereas these latter groups in turn earn more than black women and Latina women. 6 However, despite superficial appearances, the data on pay gaps don't approximate an additive account (Greenman & Xie 2008;Misra & Murray-Close 2014). Specifically, the gender pay gap is larger between white men and white women than it is between men and women of other groups, and the racial pay gap is larger among men than it is among women.…”
Section: Motivating Intersectionalitymentioning
confidence: 99%